Stearidonic‐Enriched Soybean Oil Modulates Obesity, Glucose Metabolism, and Fatty Acid Profiles Independently of Akkermansia muciniphila. Issue 17 (26th July 2020) - Segura Munoz, Rafael R.; Quach, Truyen; Gomes‐Neto, João C.; Xian, Yibo; Pena, Pamela A.; Weier, Steven; Pellizzon, Michael A.; Kittana, Hatem; Cody, Liz A.; Geis, Abby L.; Heck, Kari; Schmaltz, Robert J.; et al.
Abstract : Scope: Previous studies have suggested that diets rich in omega‐3 and low in omega‐6 long‐chain polyunsaturated fatty acids (PUFAs) can limit the development of metabolic syndrome (MetS). Transgenic soybeans yielding oils enriched for omega‐3 PUFAs represent a new and readily‐available option for incorporating omega‐3 PUFAs into diets to provide health benefits. Methods and Results: Transgenic soybean oils, enriched for either stearidonic acid (SDA) or eicosapentaenoic acid (EPA), are incorporated into diets to test their effects on limiting the development of MetS in a mouse model of diet‐induced obesity. Supplementation with SDA‐ but not EPA‐enriched oils improved features of MetS compared to feeding a control wild‐type oil. Because previous studies have linked the gut microorganism Akkermansia muciniphila to the metabolic effects of feeding omega‐3 PUFAs, the causal contribution of A. muciniphila to mediating the metabolic benefits provided by SDA‐enriched diets is investigated. Although A. muciniphila is not required for SDA‐induced metabolic improvements, this microorganism does modulate levels of saturated and mono‐unsaturated fatty acids in host adipose tissues. Conclusion: Together, these findings support the utilization of SDA‐enriched diets to modulate weight gain, glucose metabolism, and fatty acid profiles of liver and adipose tissue. Abstract : Feeding transgenic soybeans oils enriched in stearidonic acid (SDA) limits the development of metabolic syndrome and increases incorporation of n‐3 polyunsaturated fatty acids (PUFAs) in liver and adipose tissue in mice. The gut microorganism Akkermansia muciniphila is not required for SDA‐induced metabolic improvements; however, A. muciniphila modulates levels of saturated and mono‐unsaturated fatty acids in host adipose tissues.